Pengaruh Rasio CAMEL Terhadap Potensi Financial Distress - pryangan, wulandari wulan (Universitas Pendidikan Indonesia, 2020)
The purpose of this study is to examine the effect of the CAMEL ratio on the potential for financial distress in rural banks in the Central Java region for the 2017-2018 period. The population chosen in this study were rural banks in the Central Java region for the 2017-2018 period. The method used for sampling in this study was purposive sampling technique. 229 BPRs were the sample for the study with a period of 2 years in order to obtain 458 observational data. The data analysis used is logistic regression analysis using SPSS 20 software. The results prove that the CAR and ROA variables have a significant positive effect on the potential for financial distress, the NPM variable has a significant negative effect on the potential for financial distress, while the PPAP and LDR variables have no effect on potential financial distress.Keywords: Potential Financial Distress, CAMEL Ratio